Interdomain plant–microbe and fungi–bacteria ecological networks under different woodland use intensity during the dry and wet season - Li, Jing; Li, Shuaifeng; Huang, Xiaobo; Lang, Xuedong; Tang, Rong; Zhang, Rui; Su, Jianrong (Frontiers in Ecology and Evolution, 2023)
Microbial communities, which are affected by soil types and climate factors, contribute to maintain the function of terrestrial ecosystems. Recent studies have shown that interdomain relationships in below-aboveground communities may contribute greatly to ecosystem functioning. However, the responses of interactions among plant, soil fungal, and bacterial communities to the change of woodland use and their effects on ecosystem multifunctionality (EMF) remain poorly understood. In this study, the plant-microbe and fungi-bacteria interdomain ecology network (IDEN) based on SparCC pairwise associations were constructed by simultaneous aboveground plant surveys and belowground microbial analyses among four different woodland use intensities (WUI) along different seasons. The effects of different seasons on these relationships were surveyed to probe into the links to EMF. With the increase of woodland use intensity, the plant-microbe network complexity decreased, while the fungus-bacteria network complexity increased. In both dry and wet seasons, ecosystem multifunctionality decreased with the increase of woodland use intensity. Some tree species are the network hubs and may play a pivotal role in the community structure stability of the forest ecosystem. During the dry season, WUI could indirectly affect EMF through plant-microbial network complexity. During the wet season, WUI had a direct effect on EMF. WUI also indirectly affected EMF through plant-microbial network complexity and fungus-bacterial network complexity. Air temperature is the main climatic factor for EMF in the dry season, while soil moisture content is the climatic factor for EMF in the wet season. Our study revealed the important role of the relationship between plants and their associated soil microbial communities (IDENs) in maintaining ecosystem processes and function. Investigating the recovery dynamics of inter-domain ecological networks after extreme disturbances is important for understanding the overall development of ecosystems.